2005
DOI: 10.1007/s10350-004-0867-6
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Lateral Sphincterotomy for Chronic Anal Fissure

Abstract: Controlled lateral sphincterotomy could be a way of overcoming the risk of incontinence with lateral internal sphincterotomy for chronic anal fissure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 15 publications
1
18
0
1
Order By: Relevance
“…Similar results were also reported by other researchers like Cho et al [20], and Milito et al [21] who observed no recurrence. However Casillas et al [22] reported 5.6% recurrence of fissure in ano.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were also reported by other researchers like Cho et al [20], and Milito et al [21] who observed no recurrence. However Casillas et al [22] reported 5.6% recurrence of fissure in ano.…”
Section: Discussionsupporting
confidence: 82%
“…Recent innovations in nonsurgical alternatives such as chemical sphincterotomy have included topical nitrates (glyceryl trinitrate or isosorbide dinitrate) or botulinum toxin injections targeted at relaxation of internal anal sphincter, but these alternatives are far less effective [5][6][7][8][9]. Randomized trials have revealed that topical glyceryl trinitrate is inferior to both botulinum toxin and LIS in providing symptom relief [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…anorectal surgery, radiation or obstetrical trauma). To minimize this risk, several authors have tried a more limited division of internal sphincter, a tailored or controlled sphincterotomy [17,18]. Tailored sphincterotomy reduces the risk of incontinence, but may increase the incidence of recurrence [17,18].…”
Section: Discussionmentioning
confidence: 99%